Protein kinase activity of phosphoinositide 3-kinase regulates cytokine-dependent cell survival. - Daniel Thomas (Public Library of Science (PLoS), 2013)
The dual specificity protein/lipid kinase, phosphoinositide 3-kinase (PI3K), promotes growth factor-mediated cell survival and is frequently deregulated in cancer. However, in contrast to canonical lipid-kinase functions, the role of PI3K protein kinase activity in regulating cell survival is unknown. We have employed a novel approach to purify and pharmacologically profile protein kinases from primary human acute myeloid leukemia (AML) cells that phosphorylate serine residues in the cytoplasmic portion of cytokine receptors to promote hemopoietic cell survival. We have isolated a kinase activity that is able to directly phosphorylate Ser585 in the cytoplasmic domain of the interleukin 3 (IL-3) and granulocyte macrophage colony stimulating factor (GM-CSF) receptors and shown it to be PI3K. Physiological concentrations of cytokine in the picomolar range were sufficient for activating the protein kinase activity of PI3K leading to Ser585 phosphorylation and hemopoietic cell survival but did not activate PI3K lipid kinase signaling or promote proliferation. Blockade of PI3K lipid signaling by expression of the pleckstrin homology of Akt1 had no significant impact on the ability of picomolar concentrations of cytokine to promote hemopoietic cell survival. Furthermore, inducible expression of a mutant form of PI3K that is defective in lipid kinase activity but retains protein kinase activity was able to promote Ser585 phosphorylation and hemopoietic cell survival in the absence of cytokine. Blockade of p110α by RNA interference or multiple independent PI3K inhibitors not only blocked Ser585 phosphorylation in cytokine-dependent cells and primary human AML blasts, but also resulted in a block in survival signaling and cell death. Our findings demonstrate a new role for the protein kinase activity of PI3K in phosphorylating the cytoplasmic tail of the GM-CSF and IL-3 receptors to selectively regulate cell survival highlighting the importance of targeting such pathways in cancer.